2020
DOI: 10.1038/s41598-020-58626-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immune response and protective efficacy of porcine reproductive and respiratory syndrome virus modified-live vaccines against co-challenge with PRRSV-1 and PRRSV-2

Abstract: Cell-mediated immunity (CMI), IL-10, and the protective efficacy of modified-live porcine reproductive and respiratory syndrome virus (PRRSV) vaccines (MLV) against co-challenge with PRRSV-1 and PRRSV-2 (HP-PRRSV) were investigated. Seventy, PRRSV-free, 3-week old, pigs were allocated into 7 groups. Six groups were intramuscularly vaccinated with MLV, including Porcilis (PRRSV-1 MLV, MSD Animal Health, The Netherlands), Amervac (PRRSV-1 MLV, Laboratorios Hipra, Spain), Fostera (PRRSV-2 MLV, Zoetis, USA), Ingel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…These findings are consistent in field studies, where the MLV2 vaccine is also effective against respiratory disease in PRRSV-1 and PRRSV-2 concurrent endemically infected farms [ 69 , 70 , 71 ]. This dual challenge study contradicted another study, where a significant difference between MLV1 and MLV2 against dual PRRSV-1 and PRRSV-2 challenge did not occur [ 72 ]. The discrepancy between two dual challenge studies may be due to the different challenge virus used per study.…”
Section: Respiratory Diseasescontrasting
confidence: 80%
“…These findings are consistent in field studies, where the MLV2 vaccine is also effective against respiratory disease in PRRSV-1 and PRRSV-2 concurrent endemically infected farms [ 69 , 70 , 71 ]. This dual challenge study contradicted another study, where a significant difference between MLV1 and MLV2 against dual PRRSV-1 and PRRSV-2 challenge did not occur [ 72 ]. The discrepancy between two dual challenge studies may be due to the different challenge virus used per study.…”
Section: Respiratory Diseasescontrasting
confidence: 80%
“…As reviewed by Van Reeth et Ma in 2013, an intranasal route or an endotracheal route using a lower swIAV dose lead to slower and lower viral load peaks in lungs, milder lung inflammation (lower levels of IFNa, IFNg and pro-inflammatory cytokines in BALF) and less influenza-specific symptoms [ 40 ]. The MLV1 vaccination route could additionally have impacted the results obtained in this study as it was demonstrated that intramuscular PRRSV vaccination induced a lower cell-mediated immune response than intradermal vaccination [ 5 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, 98.8 percent of the PRRSV-1 vaccines sold for breeding animals in 2020 were MLV vaccines (https://vetstat.fvst.dk/vetstat/, accessed on 5 April 2021), which is in accordance with the situation in other countries. The prescription of MLV vaccines towards reproductive failure in sow herds is supported by research in the field [7][8][9][10]. However, repeated exposure of breeding animals to PRRSV MLV is often "off-label" use and may lead to negative side effects [11,12].…”
Section: Introductionmentioning
confidence: 99%